Reviews of Environmental Contamination and Toxicology - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews, 2012)
CONTENTS FOREWORD PREFACE Parameters for Pyrethroid Insecticide QSAR and PBPK/PD Models for Human Risk Assessment James B. Knaak, Curtis C. Dary, Xiaofei Zhang, Robert W. Gerlach, R. Tornero-Velez, Daniel T. Chang, Rocky Goldsmith and Jerry N. Blancato Index.